Confessions of a bi-polar mardi gras queen - Etienne, Marie (Alluvium Books, 2009)
Confessions of a bi-polar mardi gras queen is filled with thematically connected stories that swing between hilarity and devastation. One of nine children growing up in a well-to-do family in Southern Louisiana, Marie Etienne spent decades risking everything in her search for happiness, sanity, and love. As an adult, her increasingly erratic behavior mirrored the drama of her upbringing and took its toll on her two sons